G159(P) Keeping still, a case of reversible progressive paralysis in a baby. (May 2019) - Cuevas-Asturias, S; Ramnarayan, P
Abstract : Aim: To discuss the case of a baby presenting with reversible progressive paralysis due to infantile botulism. Case: This is the first case of infantile botulism in the UK since 2013 which presented after long haul travel to USA. A five month old girl with no history of illness presents with a rapidly progressing descending symmetrical paralysis. She had no significant past medical or familial history. Her initial complaint was difficulty in breast feeding followed by a rapid deterioration with hypotonia and respiratory failure. As a result, she was intubated and ventilated for 11 days whilst she was investigated extensively in paediatric intensive care. She was clinically thought to have infantile botulism and after a positive culture she was successfully treated with Baby BIG (immunoglobulin) for infantile botulism. She is back to her normal baseline. Investigations: Initial blood tests and cerebrospinal fluid analysis including cell counts, protein and glucose were normal. Echocardiogram, electro-encephalogram and nerve conduction study were normal. Needle electromyography (EMG) found small, short and polyphasic motor unit action potentials. A PCR for detection of Clostridium botulinum type B neurotoxin genes in faecal specimens was negative. The mouse assay test was only partly positive and diagnosis was eventually confirmed by stool culture. Discussion: Infantile botulism is an orphan disease that specifically affects infant less than 12 months of age. It is most commonly acquired in the United States with between 70–100 cases reported annually. In the UK it is a rare disease; there are now fourteen reported cases of infantile botulism in the UK. It is due to absorption of botulin toxin produced within the intestinal tract by temporary colonising clostridia. Infantile botulism typically presents with constipation and poor feeding. However, the clinical presentation may vary from mild hypotonia to severe bulbar paralysis and sudden infant death. It is a rare but important differential diagnosis in progressive hypotonia or paralysis in an infant in the UK. It has a completely reversible cause and effective treatment. As a result, this case highlights the importance of taking an accurate travel and diet history.